APLIKASI PENYEDIA JASA LAUNDRY ONLINE BERBASIS WEB MENGGUNAKAN PHP DAN MYSQL - Marthika Marczha; Faramita Dwitama; Ertie Nur Hartiwati (Jurnal Ilmiah Teknik, 2023)
As we know that technology is currently growing rapidly in almost all parts of the world, all circles almost use it. The use of internet is very essential in everyday life as people cannot escape from it. The internet is funtioned today by some people to provide information as a communication tool. Beside that, people also utilize the internet as a media for online laundry service providers. This website has been successfully created to make it easier for consumers who have little time because they are busy with work in terms of washing consumer clothes. This paper will discuss the creation of the website application, with application design using dreamweaver and photoshop as the interface engine and PHP and MySql as the backend database.